Barriers and Prospects of Women’s Participation in Local Governments of Nepal - Khatri, Shanta Kumari; Paudel, Naresh (The Himalayan Geographers, 2025)
This study explores both the barriers and prospects of women’s participation in local governments of Nepal, with a focus on elected women representatives in Gandaki Province. Using a mixed-methods approach, it integrates quantitative analysis of the 2017 and 2022 local election results with qualitative data from 25 semi-structured interviews and case studies. The quantitative data, sourced from the Election Commission of Nepal, show a notable increase in women’s representation due to constitutional quotas and reservation policies. However, the qualitative findings reveal that this numerical increase has not translated into meaningful participation or leadership influence. Women, particularly those from Dalit, Janajati, and other marginalized communities, remain largely confined to reserved or symbolic positions. Structural barriers such as caste-based discrimination, patriarchal social norms, political exclusion, and limited access to education and capacity-building opportunities hinder their effectiveness. Furthermore, political parties, while nominating women to fulfill quotas, often lack inclusive strategies, meaningful leadership training, and internal democratic practices that support women’s political growth. Party mechanisms frequently treat women as token figures rather than transformative leaders, limiting their engagement in decision-making processes. Despite these challenges, the study identifies emerging prospects. Women’s increasing presence in local institutions is gradually shifting traditional gender norms, and some elected representatives are beginning to assert their voices in governance and community development. Guided by an intersectional feminist framework, the study concludes that substantive participation requires not just legal inclusion but structural reforms within political parties, institutional support, and investments in women’s leadership development to achieve inclusive and democratic local governance in Nepal.